Functional and cognitive decline in hospitalized elderly - Mendes, Eugénia (2016)
Aim – Understand if functional and cognitive decline is accentuated during hospitalization in elderly patients. Method – It was design a descriptive and correlational study. The Functional Independence Measure (FIM) and the Mini-Mental State Examination (MMSE) were used. Results – Were evaluated at admission and discharge 51 elderly (75.53 ± 7.16 years), 53% women, admitted in an internal medicine unit with a length of stay of 14.27±6.45 days. For FIM and MMSE were found statistically significant differences with lower scores from admission to discharge. Negative correlations between age and length of stay and the scores of all measures were found. Except for the Cognitive FIM at admission, all elderly residents at home fared better than the institutionalized in all measures. Conclusions – The hospitalization contributes to a greater weakness/frailty of the elderly and is considered high risk for decline in physical fitness and cognitive function.